An assessment of the performance of scenarios against historical global emissions for IPCC reports. (January 2021) - Strandsbjerg Tristan Pedersen, Jiesper; Duarte Santos, Filipe; van Vuuren, Detlef; Gupta, Joyeeta; Encarnação Coelho, Ricardo; Aparício, Bruno A.; Swart, Rob
Graphical abstract: Highlights: It is essential to reassess the relevance of emissions scenarios with with long-term developments regularly. 'IPCC scenarios' did not systematically over-/underestimate historical global emissions. Historical global emissions followed a medium–high emissions pathway well within scenarios ranges. Most scenarios overestimated OECD but underestimated non-OECD CO2 and GDP growth. Adjusting SSP-BL "non-biomass renewables" & "nuclear" may be relevant for future updates. We find six overall periods of fast/slow CO2 growth (1960-2020), highlighting differences between long- vs. short-term evaluations. Abstract: Long-term emissions scenarios have served as the primary basis for assessing future climate change and response strategies. Therefore, it is important to regularly reassess the relevance of emissions scenarios in light of changing global circumstances and compare them with long-term developments to determine if they are still plausible, considering the newest insights. Four scenario series, SA90, IS92, SRES, and RCP/SSP, were central in the scenario-based literature informing the five Assessment Reports of the Intergovernmental Panel on Climate Change (IPCC) and the sixth assessment cycle. Here we analyze the historical trends of carbon dioxide (CO2) emissions from fossil fuel combustion and industry and emissions drivers between 1960 and 2017. We then compare the emission scenario series with historical trends for the period 1990–2017/2018. The results show that historical trends are quite consistent with medium scenarios in each series. As a result, they can be regarded as valid inputs for past and future analyses of climate change and impacts. Global CO2 emissions 1960–2018 (and 1990–2018) comprised six (and three) overall subperiods of emissions growth significantly higher and lower than average. Historically, CO2 emissions (in absolute numbers and growth rate) are tightly coupled with primary energy and indirectly with GDP. Global emissions generally followed a medium-high pathway, captured by "middle-of-the-road" scenario narratives in the earlier series, and by combinations of "global-sustainability" and "middle-of-the-road" narratives in the most recent series (SRES and SSP-baselines). Historical non-OECD trends were best captured by "rapid-growth" and "regional-competition" scenarios, while OECD trends were close to regional-sustainability and global-sustainability scenarios. Areas where the emissions scenarios captured the historical trends less well, are renewable and nuclear primary energy supply. The fact that the actual historical development is consistent with rapid-growth narratives in the non-OECD regions might have important implications for future greenhouse gas emissions and associated climatic change.